Analisis Penataan Arsip Dinamis Berbasis Digital di Universitas Negeri Semarang - Legowo, Djoko; Saeroji, Ahmad; Prakosa, Dwi Untung; Kurniati, Yuniar; Ismiyati, Ismiyati; Sholikah, Mar'atus (Ilmu Informasi Perpustakaan dan Kearsipan, 2021)
This study aims to determine the dynamic archive management carried out digitally by the work unit of the Faculty of Economics, State University of Semarang (UNNES). This study uses a qualitative descriptive with an interactive model. Data analysis starts from data reduction, data presentation, and drawing conclusions. Research informants are employees who manage dynamic archives in the work unit of the Faculty of Economics, UNNES who were selected using the snowball sampling technique. The findings of this study explain that the process of organizing digital-based archives is still in the planning and testing stages. In structuring digital archives, there are three stages, namely filing, borrowing, and destroying archives. Although, the work unit of the Faculty of Economics, UNNES, has conducted trials of digital-based structuring, the archive file process still uses a manual system. Next, the archive lending stage, if there are borrowers from external parties, they must fill in the digital archive system menu. This is so that the status of the archive can be known easily whether the archive is available or still borrowed. The third stage is the destruction of the archive. The work unit of the Faculty of Economics has carried out the destruction according to a predetermined archive retention schedule. Thus, the development of digital-based archive arrangement is very much needed by the work unit so that the archive arrangement process can be more effective and efficient in providing services to the academic community, especially during the COVID-19 pandemic.